2012
DOI: 10.1111/j.1365-2249.2012.04609.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic expression of CCL2 in alcoholic liver disease is associated with disease severity and neutrophil infiltrates

Abstract: SummarySerum levels and liver expression of CCL2 are increased in patients with alcoholic hepatitis (AH). In an experimental model of alcoholic liver disease (ALD), CCL2 was implicated in proinflammatory cytokines activation and hepatic lipid metabolism, but its role in human disease is currently unknown. In a large cohort of ALD patients, we analysed plasma levels and liver expression of CCL2 and their association with liver disease severity and histological lesions. We also studied the relationship between -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
66
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 27 publications
(41 reference statements)
1
66
0
Order By: Relevance
“…Besides, significant increases of the levels of Rantes, TNF-a, and NO in Hepatitis C virus-infected patients are observed [19]. Another study has shown that MCP-1 plasma levels are higher in both alcoholic liver disease and alcoholic hepatitis patients than in the controls, and alcoholic hepatitis patients have significantly higher hepatic expression of MCP-1 [20]. Our results indicated that EGCG inhibited the expression of Rantes and MCP-1, which in turn inhibited the migration of inflammatory cells into the liver, thus reducing liver injury severity.…”
Section: Discussionmentioning
confidence: 89%
“…Besides, significant increases of the levels of Rantes, TNF-a, and NO in Hepatitis C virus-infected patients are observed [19]. Another study has shown that MCP-1 plasma levels are higher in both alcoholic liver disease and alcoholic hepatitis patients than in the controls, and alcoholic hepatitis patients have significantly higher hepatic expression of MCP-1 [20]. Our results indicated that EGCG inhibited the expression of Rantes and MCP-1, which in turn inhibited the migration of inflammatory cells into the liver, thus reducing liver injury severity.…”
Section: Discussionmentioning
confidence: 89%
“…102 Among CC chemokines, CCL2 has recently been suggested to play a role in alcohol-related damage, because its liver and plasma levels were associated with disease severity and with inflammation, including neutrophil infiltration, but not with steatosis, in patients with alcoholic liver disease. 103 Interestingly, polymorphisms in the CCL2 and CCR2 genes were more frequent in patients with severe disease. These lines of evidence are supported by experimental findings in mice deficient in CCL2 fed a Lieber-DeCarli diet for 6 weeks.…”
Section: Alcoholic Liver Diseasementioning
confidence: 99%
“…Expression levels of CCL2 in the serum and liver was increased in alcoholic hepatitis patients, and this increase was pronounced in severe forms of the disease. 39 Furthermore, Ziol and colleagues 40 analyzed 35 alcoholic hepatitis patients and found that the hepatocyte apoptotic index, but not the ballooning hepatocyte index, was strongly correlated with the neutrophil infiltration index. Therefore, understanding of the role of the innate immune system, particularly the role of neutrophils, in alcoholic liver disease pathogenesis may help to identify novel therapeutic targets for this disease.…”
Section: Neutrophils and Alcoholic Liver Diseasementioning
confidence: 99%